Axial Compression Performance and Residual Strength Calculation of Concrete-Encased CFST Composite Columns Exposure to High Temperature - Xiaojun Ke; Wannian Xiang; Xiuning Peng; Yu Dan (Applied Sciences, 2022)
Concrete-encased concrete-filled steel tube (CFST) composite columns provide high bearing capacity, good seismic performance and an easier connection with arbitrary angle beams, which are widely used in high-rise buildings. Considering the high frequency of building fires, experimental research investigated the axial compressive behavior of the composite columns’ exposure to high temperature in this paper. Fourteen specimens after exposure to high temperatures with different parameters, including the heating temperature, steel tube diameter and concrete cover thickness, were fabricated to test under axial compressive loading. The failure pattern, load-displacement curve, bearing capacity, initial stiffness, deformation performance and damage rule of the specimens were discussed. The test results showed obvious differences in damage of specimens subjected to various high temperatures. The failure of the specimens began with the spalling and crushing of the concrete at the edge and ends in a lantern shape. The load-displacement curves of the specimens were significantly affected by high temperature, while the influence the of steel tube diameter and concrete cover thickness was relatively weak. A method of calculating axially loaded capacity for the composite column exposure to high temperature is proposed considering the effects of the main parameters of heating temperature and steel tube position, and the calculated results are in good agreement with the experimental results.